2020
DOI: 10.1007/s00192-020-04319-z
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal laser for overactive bladder syndrome

Abstract: Overactive bladder syndrome (OAB) is defined as urinary urgency, usually with urinary frequency and nocturia, with or without urge urinary incontinence. The prevalence of OAB in adult women ranges between 11% and 42%, is particularly common in elderly people, and can overlap with the genitourinary syndrome of menopause (GSM). There is a wide approach to the treatment of symptoms, often in a stepwise fashion, including lifestyle changes, bladder retraining and pelvic floor muscle rehabilitation, drug therapy, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…There currently is not enough evidence to suggest treatment for urinary symptoms with laser therapy. 43…”
Section: Other Treatments For Overactive Bladder In Gsmmentioning
confidence: 99%
See 1 more Smart Citation
“…There currently is not enough evidence to suggest treatment for urinary symptoms with laser therapy. 43…”
Section: Other Treatments For Overactive Bladder In Gsmmentioning
confidence: 99%
“…Like Ospemifene, some small clinical trials have shown some improvement in OAB symptoms with vaginal laser in postmenopausal women, but no large-scale randomized placebo-controlled trials have been done. There currently is not enough evidence to suggest treatment for urinary symptoms with laser therapy 43 …”
Section: Management Of Genital and Sexual Problems Of Gsm— Vulvovagin...mentioning
confidence: 99%
“…Une étude s'est intéressée au traitement de l'hyperactivité vésicale par laser appliqué au niveau vaginal et périnéal. Elle montrait une amélioration de la symptomatologie chez les quelques patientes traitées [65].…”
Section: Les Injections Intradétrusoriennes De Toxine Botuliqueunclassified